20 years of DNA Polymerase μ, the polymerase that still surprises. (25th April 2021) - Ghosh, Dipayan; Raghavan, Sathees C.
Abstract : DNA polymerases are important enzymes involved in DNA replication and repair. Based on sequence homology, DNA polymerases have been grouped into distinct families, which are A, B, X, and Y. The Pol X family consists of four members: Pol λ, μ, and β and terminal transferase or TdT. Members of the family X are involved in base excision repair, nonhomologous end joining (NHEJ), and V(D)J recombination. One of the most interesting pol X family members is DNA polymerase μ, discovered back in 2000. Subsequent studies established the importance of Pol μ as a repair polymerase in NHEJ and its interactions with the other proteins of the NHEJ machinery. Pol μ has a number of interesting properties, which sets it apart from the other known DNA polymerases, including its ability to synthesize DNA from an unpaired primer terminus as well in the complete absence of a template strand (terminal transferase activity). Another standout property of Pol μ is its reduced ability to discriminate between ribonucleotides and deoxyribonucleotides and its ability to utilize both ribonucleotides and deoxyribonucleotides as substrates during the gap‐filling stage of NHEJ. In this review, we provide a brief overview of Pol μ in double‐strand break repair and the current knowledge on its various functional aspects. Abstract : The Pol X family of DNA polymerases consists of DNA polymerases λ, μ, and β and terminal transferase (TdT). The focus of this review is DNA polymerase μ, a highly specialized and versatile DNA polymerase, which is involved in DNA repair through NHEJ and possesses several unique properties such as template‐independent synthesis activity and indiscriminate use of both rNTPs and dNTPs during DNA synthesis.